Sexism and justification of violence among ecuadorian adolescents in psychosocial risk contexts - Soto Bustamante, Rocío (2020)
The research aims to analyze the relationships between ambivalent sexism and attitudes justifying violence among peers and domestic violence (in 73 adolescents (43 females and 30 males) aged from 11 to 18 years (M = 15.74, SD = 1.14 ), from a community in psychosocial risk in Loja, Ecuador. The Attitudes towards Diversity and Violence Questionnaire (Díaz-Aguado, Martínez Arias, & Martín Seoane, 2004) was used, as well as the Inventory of Ambivalent Sexism for Adolescents (De Lemus et al., 2008). Positive relationships were obtained between the variables, where hostile sexism proved to be a strong predictor of attitudes that justify domestic violence (R2 = .40, p <.001) and violence between peers (R2 = .39, p <. 001). Therefore, on the one hand, it is relevant for communities at risk to develop violence prevention programs that promote a culture of peace and, on the other hand, the deconstruction of sexism by strengthening of their rights and empowerment of resources.